"Neighbours First, Bankers Second": Mobilising financial citizenship in Singapore. (August 2015) - Lai, Karen P.Y.; Tan, Choon Hang
Highlights: The state is a vital and strategic actor in financial subject formation and financialisation. Individual consumers are not only neoliberal financial subjects but also citizen subjects. The case study of POSB bank connects state, firm and individuals in financialisation. There is overlapping operation of sovereign and biopolitical power in financialisation. The discussion argues for a more supple analysis of Foucauldian governmentality. Abstract: While financialisation has been typically framed as a market imperative that permeates everyday life and transforms individuals and households into responsible self-governing subjects, we argue that the role of the state is vital in explaining the formation and impacts of specific forms of financial subjectivity. In particular, the state is an active agent in the production of financial citizenship through championing particular financial responsibilities and duties. As such, individual consumers are financial subjects who not only fulfil neoliberalised scripts of self-reliant and disciplined subjects able to take care of their own financial futures, they are also mobilised as citizen subjects who contribute to a stronger and more competitive national economy through their changing financial practices, even as they benefit from greater access to financial products and services. Drawing from the role of the Singapore government and the institutional development of the Post Office Savings Bank (POSB), we connect state, firm and individuals in the changing roles of financial logics in everyday life, corporate transformation, and how those feed into broader developmental objectives of Singapore's international financial centre aspiration. This supports a more supple analysis of Foucauldian governmentality by drawing out the ways in which heterogeneous elements of power—sovereign, disciplinary and biopolitical—are reconfigured and redeployed in new formations of financial subjects.